2016
DOI: 10.1007/s10518-016-9954-z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic vehicle–bridge interaction under simultaneous vertical earthquake excitation

Abstract: Traditionally, the seismic response analysis of a bridge does not account for the concurrent vehicle-bridge dynamic interaction. However, the behavior of a seismically excited bridge can jeopardize the safety of the vehicles running on it, even if the bridge itself remains undamaged. This study examines the seismic response of a vehicle-bridge interacting (VBI) system under vertical earthquake excitation, modelling the truck vehicles as rigid body assemblies. An application of the proposed scheme to a realisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 36 publications
0
18
0
1
Order By: Relevance
“…Shaban et al [12] evaluated the effects of vehicles on the seismic response of bridges by applying five different seismic excitation tests. Paraskeva et al [13] researched the dynamic response of a vehiclebridge interacting system under vertical earthquake excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Shaban et al [12] evaluated the effects of vehicles on the seismic response of bridges by applying five different seismic excitation tests. Paraskeva et al [13] researched the dynamic response of a vehiclebridge interacting system under vertical earthquake excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several studies have investigated the response of coupled systems under dynamic (earthquake) loading. 20 The seismic response for frequent, moderate, and strong earthquakes 11,21,22 is evaluated, estimating the dynamic stability and parameters that affect running safety of trains moving over bridges during earthquakes. 23,24 Furthermore, the parameters affecting the train derailment mechanism during earthquakes are explored.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, consistent with the explanation of TMD effect, even if the seismic response of bridge is reduced the vibration of vehicle will probably be consequentially increased. This means vehicle may possibly lose contact with bridge deck 6,17 or even roll over just as those seismic induced vehicle accidents observed in past earthquake events. 9 And drivers usually found that it is hard to control the vehicle at the outbreak of earthquakes due to excessive vehicle responses.…”
Section: Introductionmentioning
confidence: 99%